2014
DOI: 10.1590/1516-635x1603313-318
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid model of uniform design and artificial neural network for the optimization of dietary metabolizable energy, digestible lysine, and methionine in quail chicks

Abstract: KeywordsQuail chick, nutritional requirement, uniform design, neural network.Submitted: September/2013 Approved: June/2014 ABSTRACT A uniform design (UD) was used to construct models to explain the growth response of Japanese quails to dietary metabolizable energy (ME), and digestible methionine (dMet) and lysine (dLys) under tropical condition. In total, 100 floor pens with seven birds each were fed 25 UD different diets containing 25 ME (2808-3092 kcal/kg), dMet (0.31-0.49% of diet), and dLys (0.91-1.39% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Each model consisted of linear or non-linear parameters (compartments) that could be converged to make a mathematical equation relating the nutrient doses with animal responses. In general, the biological models follow the non-linear manner that has been illustrated in different platforms, including broken lines [ [9] , [10] , [11] , 28 , 29 ], response surface methodology [ [30] , [31] , [32] ], uniform design [ 33 ], artificial neural networks [ 34 , 35 ], and three or four-parameter models [ 36 ] by researchers. The other methods used to estimate the amino acid requirements in monogastric animals are the non-linear logistic and saturation kinetic models [ 37 , 38 ], Rayleigh [ 36 ], and exponential models [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each model consisted of linear or non-linear parameters (compartments) that could be converged to make a mathematical equation relating the nutrient doses with animal responses. In general, the biological models follow the non-linear manner that has been illustrated in different platforms, including broken lines [ [9] , [10] , [11] , 28 , 29 ], response surface methodology [ [30] , [31] , [32] ], uniform design [ 33 ], artificial neural networks [ 34 , 35 ], and three or four-parameter models [ 36 ] by researchers. The other methods used to estimate the amino acid requirements in monogastric animals are the non-linear logistic and saturation kinetic models [ 37 , 38 ], Rayleigh [ 36 ], and exponential models [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used several regression models, five types of broken line models and the quadratic polynomial, to estimate the lysine requirement of growing quails. Different models and design of experiments (DOE) have been used for estimation of nutritional requirements in birds and domestic animals (Baker, Batal, Parr, Augspurger, & Parsons, 2002;De Leon, Kidd, & Corzo, 2010;Ghazaghi, Mehri, Yousef-Elahi, & Rokouei, 2012;Mehri, 2012Mehri, , 2014Mehri, Davarpanah, & Mirzaei, 2012;Mehri & Ghazaghi, 2014;Mehri, Nassiri Moghaddam, Kermanshahi, & Danesh-Mesgaran, 2013;Mercer, 1992) but as Pesti et al (2009) suggested, each model may have some advantages and disadvantages. For instance, although second-order polynomials are easy to fit to data, the inclusion of input data below or above those points that are required for maximum or minimum responses, resulting in remarkable changes in requirement estimates ).…”
Section: Discussionmentioning
confidence: 99%
“…e UD method has attracted attention in many studies in various fields [42][43][44][45][46] because it has the following distinct characteristics: space filling, robustness, and multiple levels [40,41]. ese characteristics have led to the UD method becoming one of the major current experimental design approaches in China.…”
Section: Introductionmentioning
confidence: 99%